PENGEMBANGAN LKPD DENGAN PENDEKATAN PROBLEM BASED LEARNING BERBANTUAN SCRATCH UNTUK MENINGKATKAN KETERAMPIAN PEMECAHAN MASALAH MATEMATIS SISWA - Widiyanti, Sri Indah; Desniarti, Desniarti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to find out whether the LKPD is based on problem based learning on statistica material to improve the problem solving abilities of class VII students in a feasible, practical and effective way in the learning process. This research uses the Research and Development (ReDi research method with the ADDIE (Analyze. Design, Development, Implementation. Evaluation) model. The research instrument uses validation sheets, questionnaires and tests. The results of this research indicate that the LKPD based on problem based learning to improve students' problem solving abilities that has been developed is valid and feasible to apply with a percentage of 94% (media experts) and 84% (material experti). The LKPD was also stated to be practical at seen from the teacher response questionnaire with a percentage of 100% and the student response questionnaire of 91.78% The LKPD was declared effective as seen from the N-Gain score of 0 6632 in the "High" category. Students' problem solving abilities also increased as seen from the prelest results of 58.75% (Poor) and posttest of 81.41% (Very Good). Based on the research results, it can be concluded that problem-based learning LKPD to improve the problem-solving abilities of class VII students has been developed which is feasible, practical and effective to use. The developed LKPD can increase students' learning activities and teachers can use LKPD as teaching materials In the learning process. is a brief overview of the entire content of the article so that it contains Background